The call of the wild - London, Jack, 1876-1916. (New York : Tor, 1990)
Jack London's classic tale tracing Buck's entry into the wild and survival among the wolves.
"A Tom Doherty Associates book.".
"Complete and unabridged"--Cover.
Wilson's Children.
Wilson's Junior High School.
Wilson's Senior High School.
6.0
Keywords: Dogs -- Fiction; Wolves -- Fiction; Dogs -- Fiction; Wolves -- Fiction